2016
DOI: 10.1159/000448596
|View full text |Cite
|
Sign up to set email alerts
|

Resident Involvement in Radical Inguinal Orchiectomy for Testicular Cancer Does Not Adversely Impact Perioperative Outcomes - A Retrospective Study

Abstract: Introduction: To evaluate perioperative outcomes related to resident involvement (RI) in a large and prospectively collected multi-institutional database of patients undergoing orchiectomy for testicular cancer. Materials and Methods: Using current procedural terminology and ICD-9 codes, information about patients with testicular cancer were abstracted from the American College of Surgeons National Surgical Quality Improvement Program database (2006-2013). Multivariable analyses evaluated the impact of RI on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Matulewicz et al reported that the residents' population had significantly higher operative times and hospital stays, which is also reported by Kern et al, Aisen et al, Allard et al, Yip et al23,24,26,33,34 Although the presence of residents was significantly associated with increased operative time in the performed surgeries, the length of hospital stay was not significantly different from the nonresident group, in the studies by Meyer et al, and Vetterlein et al, Benjamin et al, and Privé et al reported that longer operative time was associated with the residents' group, however, no complications were significantly noticed.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…Matulewicz et al reported that the residents' population had significantly higher operative times and hospital stays, which is also reported by Kern et al, Aisen et al, Allard et al, Yip et al23,24,26,33,34 Although the presence of residents was significantly associated with increased operative time in the performed surgeries, the length of hospital stay was not significantly different from the nonresident group, in the studies by Meyer et al, and Vetterlein et al, Benjamin et al, and Privé et al reported that longer operative time was associated with the residents' group, however, no complications were significantly noticed.…”
supporting
confidence: 52%
“…Based on the NSQIP data also, Meyer et a, Vetterlein et al and Yip et al investigated similar outcomes in patients that underwent one-stage anterior urethroplasties, orchiectomy, minimally-invasive, and male infertility procedures, respectively. [24][25][26] They reported that the presence of residents was not a significant predictor for the occurrence of adverse events and complications. This was also supported by Privé et al, Allard et al and Del Rosso et al that reported that although residents induced some complications, these were managed intraoperatively.…”
Section: The Risk To Develop Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Orchidectomy also serves the purpose of providing tissue for diagnosis and risk stratification to determine further management including chemotherapy [41]. Inguinal orchidectomy for testicular cancer can be performed as a day case procedure, reducing pressure on beds [42]. Therefore, radical orchidectomy is high priority and should be performed whenever possible.…”
Section: Testicular Cancermentioning
confidence: 99%